Factores clave en la biología de hiperparasitoides heteronomos (Hym.: Aphelinidae): Agentes para el control biológico de mosquita blanca y escamas - Penagos, Dora I.; Williams, Trevor (Instituto de Ecología, A.C., 1995)
Whiteflies and scale insects are major pests. The use of aphelinid parasitoids (Hym.: Aphelinidae) of these pests in programs of classical biocontrol has met with unparalleled success. Many aphelinids have a remarkable form of reproduction in that host relations differ for each sex. Female parasitoids of this group always develop as primary endoparasitoids of Homoptera (e.g. whitefly nymphs) while male development is different and has been used for classification. The most intriguing of these parasitoids are the "heteronomous hyperparasitoids" in which males develop as hyperparasitoids of females of their own, or a related species. New changes have simpiified the classification of this group and have drawn attention to the flexible nature of male host relations in the majority of cases. We review aspects of the biology of heteronomous hyperparasitoids with relevance to biocontrol including host range, development, adult longevity, fecundity, ovipositional behaviour and patterns of host exploitation. The selection of the type of host and the sex ratio of the progeny are intimately linked in heteronomous hyperparasitoids. A recent theory has argued that factors which limit the reproduction of heteronomous hyperparasitoids will influence the sex ratios of fieid populations of these insects. The theory predicts that the sex ratio ot individual females will be affected by the rate of discovery of hosts and the availability of eggs. New data support these predictions. Other potentially important factors inelude local mate competition and the presence of sex-ratio distorting micro-organisms in aphelinids. The ability of heteronomous hyperparasitoids to preferentiatly attack non-conspecifics for male produclion has implications for the use of these wasps for biocontrol. Heteronomous hyperparasitoids appear to have marked competitive abilities in systems containing conventional parasitoids. Careful evaluation of the probable impact of heteronomous hyperparasitoids are required prior to fieid release in systems where conventional parasitoids already offer appreciable leveis of pest control. The remarkable biology of these parasitoids may account for past successes, but also serves as a basis for contemporary caution.